2008
DOI: 10.1007/s11606-008-0504-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Computerized Physician Order Entry with Clinical Decision Support on the Rates of Adverse Drug Events: A Systematic Review

Abstract: CONTEXT: Computerized physician order entry (CPOE) with clinical decision support (CDS) has been promoted as an effective strategy to prevent the development of a drug injury defined as an adverse drug event (ADE). OBJECTIVE:To systematically review studies evaluating the effects of CPOE with CDS on the development of an ADE as an outcome measure.DATA SOURCES: PUBMED versions of MEDLINE (from inception through March 2007) were searched to identify relevant studies. Reference lists of included studies were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
170
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(182 citation statements)
references
References 40 publications
4
170
0
2
Order By: Relevance
“…Better performance might be expected with additional decision support 15,16 . In a systematic review that evaluated the effect of CPOE with CDS on reducing ADEs, five out of ten studies showed a significant reduction of ADEs 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Better performance might be expected with additional decision support 15,16 . In a systematic review that evaluated the effect of CPOE with CDS on reducing ADEs, five out of ten studies showed a significant reduction of ADEs 17 .…”
Section: Discussionmentioning
confidence: 99%
“…4 Furthermore, certain MU functionalities such as CPOE, electronic prescribing and clinical decision support have been associated with improvements in care. 2,[23][24][25][26][27][28][29][30] However, the full clinical benefits of MU have yet to be empirically evaluated and warrant future research. Although adoption of many functionalities varied by specialty, adoption of several functionalities associated with e-prescribing significantly increased between 2009 and 2011 across both primary care physicians and specialists.…”
Section: %)mentioning
confidence: 99%
“…Its administration may be in response to an overdose of potassium, a side effect of a medication, or the result of a drug-drug interaction. Additionally, we added "yeast infection related to antibiotics" and "platelet count <50,000×10 6 /μl" as triggers, and excluded lidocaine, gentamicin, tobramycin, amikacin, vancomycin, and theophylline levels in our adaptation of the tool.…”
Section: Methodsmentioning
confidence: 99%
“…5,6 These studies have influenced policymakers 7 and consumer advocates 8,9 to promote the nationwide adoption of CPOE as a safety-driven initiative. However, despite this mandate, CPOE has not yet achieved significant market penetration.…”
Section: Introductionmentioning
confidence: 99%